Pengolahan Nugget Lele Kelor dalam Mengoptimalkan Pangan Lokal dan Pencegahan Stunting Kecamatan Geneng - Atmojo, Titin Andriyani; Nadhifah, Fairuz; Musi, Ngani Alwirya; Firmansyah, Anwar; Budi I, Muhammad Zulfa; Fauzian S., Mukhlis Althaf (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2025)
Stunting remains a significant challenge in efforts to improve the quality of life. One of the main causes is the lack of balanced nutritional intake for children during their early developmental years. The village of Dempel, located in Geneng Subdistrict, Ngawi Regency, possesses local resources such as catfish and moringa leaves, which are rich in nutrients but have yet to be fully utilized. This community service program aims to empower PKK cadres in the village of Dempel by introducing an innovative approach to processing fortified catfish nuggets with moringa leaves. The program was on Wednesday 16 January 2025 and the method used is conducted using the Community Development (ComDev) method, starting with problem identification discussions with partners, followed by program design, and finally implementing training sessions. The initiative garnered great enthusiasm from the women participants, as it taught them new skills that could be directly applied in their daily lives. Through this program, it is expected that PKK cadres will not only be able to provide healthy food for their families but also create new business opportunities that can enhance household welfare.